1998
DOI: 10.1038/sj.leu.2401175
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cellular anthracycline resistance in childhood acute leukemia

Abstract: Cellular resistance to anthracyclines is often associated with an unfavorable clinical outcome in a variety of cancers, including leukemia. Several mechanisms of anthracycline resistance may be involved such as an impaired transport of drugs across the plasma membrane, an increased drug efflux, an increased intracellular detoxification of drugs, a reduced availability of intracellular drug targets, or a reduced ability of cells to induce apoptosis. Here, we review the studies published about mechanisms which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 131 publications
0
10
0
Order By: Relevance
“…Because a single agent can induce cross‐resistance to dissimilar chemotherapeutic drugs (Den Boer et al , 1998), we tested parental and drug‐resistant cell lines for multidrug resistance (Fig 2A–F respectively). We found that DNR resistant Jurkat cells showed a 310‐fold ( c. 0·80–250 nmol/l) increase in resistance to VCR, and a 120‐fold ( c. 3·1–380 nmol/l) increase in resistance to PRED (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because a single agent can induce cross‐resistance to dissimilar chemotherapeutic drugs (Den Boer et al , 1998), we tested parental and drug‐resistant cell lines for multidrug resistance (Fig 2A–F respectively). We found that DNR resistant Jurkat cells showed a 310‐fold ( c. 0·80–250 nmol/l) increase in resistance to VCR, and a 120‐fold ( c. 3·1–380 nmol/l) increase in resistance to PRED (Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally induced drug resistance in several leukaemic cell lines through the sequential escalation of drug dosage has provided insights into the underlying mechanisms of treatment failure (Beck, 1983; Den Boer et al , 1998; Sonneveld, 2000; Aslanian et al , 2001; Liu et al , 2002; Efferth et al , 2006; Munteanu et al , 2006). Nevertheless, only the CCRF‐CEM, MOLT‐4 and Jurkat T‐ALL cell lines have been developed to show drug resistance to anthracyclines, vinca alkaloids, glucocorticoids, or l ‐asparaginase ( l ‐asp).…”
mentioning
confidence: 99%
“…Drug resistance in adult ALL may be associated with activation of antiapoptotic pathways as a consequence of aberrant growth signalling, resulting from the bypassing of normal growth factor signalling pathways in malignant cells ( Baserga, 1994). Glucocorticoids, cytosine arabinoside and anthracyclines are thought to act on the proapoptotic pathway ( Alnemri et al , 1992 ; Kaspers et al , 1994b ; Den Boer et al , 1998 ; < Savasan et al , 1998 ). Probably, the other drugs also have a proapoptotic mechanism of action, and apoptosis resistance may play a role in the resistance to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracyclines efficiently arrest cell division and induce apoptotic cell death by intercalation with DNA, generation of free radicals, interaction with cellular membranes, and inhibition of topoisomerase II (Gewirtz, 1999; Hussein, 2007). However, drug resistance and side effects such as cardiotoxicity seriously limit their clinical success (Shan et al , 1996; Den Boer et al , 1998), and it is critical to understand their intracellular metabolism and pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cell resistance toward anthracyclines, intrinsic or acquired, is induced by multiple factors, such as multidrug resistant protein expression, apoptotic pathway alterations, and drug-detoxifying enzyme induction (Gianni, 1997; Den Boer et al , 1998; Gottesman, 2002; Hembruff et al , 2008). Intracellularly, anthracyclines are metabolized by either glycosidic cleavage of bio-functional glycosidic amino sugar or reduction of ketonic groups.…”
Section: Introductionmentioning
confidence: 99%